(untitled) (Medical Forum Monthly, 2023)
Objective: To observe the association between family planning messages and knowledge, attitudes, and practices of contraception in Karachi. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Community Health Sciences, Bahria University of Health Sciences Campus Karachi from April 1st to July 15th, 2021. Materials and Methods: The data was collected via an online questionnaire incorporated in Google Form. Epi Info version 7.2.5 was used to calculate a sample size of 346. The sampling method was convenience sampling. Chi-square test was used to analyze data using SPSS version 23. Results: Most of the participants were females with mean age of 35.5 ± 20. The study results showed that persuasion to use contraceptives because of family planning messages was associated with participants knowledge and self-belief in family planning. Out of total 346 participants, participants who persuaded to use contraceptives because of family planning messages and had knowledge of family planning were higher (69.1%) than who were not persuaded (23.7%). X2(2) = 24.358, p = 0.000. Likewise, participants who were persuaded and believed that family planning is of benefit was higher (67.3%) than who were not persuaded (18.5%). X2(2) = 55.179, p = 0.000. Conclusion: The study highlights the potential of media and the internet in promoting family planning usage. However, it also emphasizes the importance of considering cultural and social factors when designing effective family planning campaigns.